Poster Session PB3 (Alcohol and alcoholism (Oxford), 2007)
PB3-1 Alcohol use pattern assessment and its relation with social-demographic variables among patients of primary health care (PHC) Ronzani TM, Amato TC, Silveira PS, Oliveira JS, Lourenço LM, Furtado EF (Brazil) Aims. The article's main goal is to assess the alcohol use pattern among patients of Juiz de Fora (Brazil) city's Primary Health Care, and to investigate the impact of social-demographic variables upon that usage pattern. Methods. Data were gathered through a structured interview and application of AUDIT (Alcohol Use Disorders Identification Test) among PHC service users. Chi-square test followed by Odds Ratio were applied in the analysis of categorical variable. After the verification of normal distribution through Kolmogorov-Smirnov, the Spearman's correlations and Non-Parametric Tests-such as Kruskal-Wallis and Mann-Whitney were followed. The significance level adopted was 97% (p < 0.03). Results. The sample comprises 371 patients, age 18 through 85 (mean = 42.8/SD = 15.7): 59% were women; 71.4% had some Elementary School, and 28,6% had some High School. As for the sample distribution of the AUDIT's classification risk zone: 52.8% were abstemious; 29.1% were low risk users; 12.7% at-risk drinkers; 1.1% harmful drinkers and 4.3% were likely dependent. There was a 2.7 higher incidence of dependents with some High School. However, the latter showed twice as much at-risk drinkers respondents (20.8%). At-risk drinkers percentage among other unspecific religions (26.7%) was seven fold bigger than the Evangelicals (3.6%). Church goers showed the greatest percentage of abstemious (62.8%), whereas non-faithful displayed a percentage of 5.5 fold more harmful drinkers (2.2%). There was a ratio of three times more at-risk participants (18.2%) or dependent (6.3%) participants younger than 43 years of age. The ratio of harmful drinkers was three times smaller (1.7%). Males showed a dependent ratio six fold bigger (8.6%). Variables which displayed significant statistical differences related to at-risk or non-at-risk drinkers were: religion (30.8% of non-religious people fell under the category of at risk users); gender (OR = 0.22) −90.9% females did not fall under the at-risk users; age (OR = 3.32) −89.4% of the interviewers aged 43 or older are not at-risk drinkers; finally church goers appeared as having 87.6% of non-at-risk drinkers (OR = 0.37). As for AUDIT scores, a weak negative correlation (R = 0.21/p = 0.000) regarding the respondents' age was detected. There was a statistical relevance between the average of categories such as gender, civil status, religion, Church goers, working or non-working, and education level. Audit mean score was bigger for men (M = 5.8/SD = 8.0), for non-faithful (M = 5.2/SD = 6.9), for non-working (M = 3.1/SD = 6.7) and High School respondents (M = 3.9/SD = 5.3). The average among single people (M = 5.9/SD = 8.3), was significantly larger than among married ones (M = 2.7/SD = 5.1); divorced (M = 1.5/SD = 3.7) and widowed (M = 0.4/SD = 0.8). It was also found out that the average for Evangelicals (M = 1.9/SD = 5.4) was exceedingly smaller if compared to Catholics (M = 4.0/SD = 6.5), non religious people (M = 5.7/SD = 6.0) and other or unspecific religious people (M = 7.0/SD = 8.2). The variable that did not display any relevant outcome in the analysis was family income. Conclusions. Most of the respondents reported to be alcohol low risk users. However, almost 20% of the target population are at least at-risk drinkers. This number is overwhelming if we consider all the harm that can befall the individual, the society and the health expenses. The research outcome also discloses that alcohol use pattern is mainly related to education, religion, age, gender, religion practices and civil status. Being younger than 43 years old appeared as a risk factor for at-risk drinkers, and being a female and Church goers were protection factors. The current paper has pointed to certain population features that need to be addressed in order to be useful in the decision making of public policies, in prevention practices, and in public health improvement. PB3-2 Harmful alcohol use in a Finnish population sample based on Alcohol Use Disorder Identification Test (AUDIT) Von der Pahlen B, Santtila P, Harlaar N, Witting K, Varjonen M, Jern P, Johansson A, Sandnabba NK (Finland) Aims. The purpose of the study was to explore the factor structure of the Alcohol Use Disorder Identification Test (AUDIT), to investigate the effects of age and gender on AUDIT composite scores, and to explore the prevalence rates of harmful drinking associated with various cut-off scores in a Finnish population sample. Methods. The AUDIT was completed by 10524 participants with a mean age of 26.2 (SE = 0.20) for males and 26.1 (SE = 0.08) years for females. The proportion of female respondents was 65.8%. The exploratory factor analyses suggested a two factor solution for both men and women. In these solutions the first three items loaded on one factor and the rest on a second factor. Results. There was a significant difference between men (7.5%) and women (10.5%) with regard to abstaining from alcohol (F1, 5058) = 1.433, p < 0.000). Age and gender and their interaction explained approximately 10% (R2 =. 098) of variation in the AUDIT composite score. The highest AUDIT mean score in men was observed in the age group from 22 to 25 years (M = 10.37, SE = 0.25) and the lowest in the age group over 34 (M = 7.5, SE = 0.47). For females there was a clear linear relationship with the highest scores attained by the age group from 18 to 21 (M = 7.2, SE = 0.18) and the lowest for females over 34 years (M = 4.5, SE = 0.21). At a cut-off score of 8 or more 48.3% of the men and 23.2% of the women were identified as having harmful alcohol use. When the percentage of people with harmful drinking for all subjects was calculated with varying cut-off scores from 6 to 11 there was a significant (p < 0.001) difference between genders. Conclusions. This is one of the largest known general population studies on alcohol use in recent years in Finland. It is suggested that the cut-off scores should be tailored according to age, gender and drinking culture. PB3-3 The level and structure of alcohol-related mortality in Grodno, Belarus Razvodovsky YE, Steackley A (Belarus) Introduction. Although alcohol seems to be an important contributor to the burden of disease in the countries of Eastern Europe, little systematic research has been undertaken on its impact on mortality in the former Soviet republic Belarus. This is especially true as regards Belarus where since 1994 falling birth rates and high mortality rates have resulted in depopulation. Aims. The aim of the present study is to address this particular deficit concerning alcohol-related mortality in Belarus by using regional-level data drawn from death certificates. Methods. All death certificates for the year 2002 in the province of Grodno were collected and examined for information concerning the presence of alcohol as either a direct or an underlying cause of death. Results. 4.2% of all deaths were alcohol-related with acute causes of death predominating. The rate of male alcohol-related mortality was far higher than the female rate. Alcohol also had a much greater impact on mortality among rural men and women compared with their urban counterparts with a rural man's life expectancy reduced by two years from birth due to the effect of alcohol-related mortality. Conclusion. Alcohol is having a particularly negative effect on mortality in Belarus. There may be a number of factors underlying this ranging from the pattern of drinking and use of surrogates through to the imbalanced population structure in rural areas. PB3-4 The post dependent state—modeling plasticity of clinical relevant, intermediate phenotypes of alcoholism Sommer WH, Rimondini R, Hansson AC, Heilig M (USA) Aims. The primary clinical features of alcoholism are loss of control over alcohol intake and complusive consumption patterns. The condition develops over years through a history of repeated cycles of intoxication and withdrawal thereby incurring a major shift from initially positive to predominantly negative reinforced drug taking. This in turn has been postulated to result from neuroadaptations that lead to a progressive recruitment of anti-reward systems, i.e. negative reinforcement through stress and fear systems involving among others extra-hypothalamic corticotrophin-releasing hormone (CRH) neurotransmission. This theoretical framework has proven useful for the design and selection of model phenotypes with good predictive validity for medication development. Methods and Results.We previously demonstrated that prolonged exposure of rats to repeated cycles of ethanol vapor intoxication and withdrawal results in a long-term up-regulation of voluntary alcohol intake that is selective sensitivity to the clinically effective drug acamprosate, which does not suppress non-dependent alcohol drinking. The most relevant signs of behavioral plasticity are 1) a persistant motivation for excessive voluntary alcohol consumption, 2) an increased behavioral sensitivity to stress, and 3) long-lasting functional tolerance to the hypnotic effects of ethanol despite normal ethanol metabolism and elimination. Collectively this behavioral syndrom is labeled ‘post-dependent’ state. As predicted an upregulation of the amygdala corticotrophin-releasing hormone (CRH) system. Microarray screening points to further candidates with long-lasting changes in gene expression in medial prefrontal cortex, nucleus accumbens and amygdala. Several compounds besides acamprosate have been tested in post dependent animals, among them the CRH receptor 1 antagonists antalarmin and MTIP and show specific suppression of excesive ethanol consumption. Conclusions. The post-dependent state models some of the prominent clinical features of alcoholism and has predictive v